1995
DOI: 10.1111/j.1475-6765.1995.tb00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Government ‘strength’ and budget deficits in advanced democracies

Abstract: Abstract. Roubini and Sachs provided the first systematic test of the idea that political structure the size, composition, diversity, and/or stability of a governing cabinet ‐ is related to budget deficits. In this paper, we take issue with several of Roubini and Sachs' choices concerning data and operationalization, and argue that their approach cannot offer clear conclusions about the relationship between national political structure and budget deficits. We test the ‘strength of government’ hypothesis using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…They found a positive association between government fragmentation and fiscal deficits in their sample of OECD countries. Similar results were found in other studies, such as Edin and Ohlsson (1991), Borrelli and Royed (1995), Franzese (2000), Volkerink and De Haan (2001) and Balassone and Giordano (2001), among others. In a similar vein, other papers also found that more fragmented governments seem to be less prone to introducing fiscal adjustments in response to adverse economic shocks (Alesina and Drazen 1989).…”
Section: 2 Government Fragmentation and Fiscal Outcomessupporting
confidence: 80%
“…They found a positive association between government fragmentation and fiscal deficits in their sample of OECD countries. Similar results were found in other studies, such as Edin and Ohlsson (1991), Borrelli and Royed (1995), Franzese (2000), Volkerink and De Haan (2001) and Balassone and Giordano (2001), among others. In a similar vein, other papers also found that more fragmented governments seem to be less prone to introducing fiscal adjustments in response to adverse economic shocks (Alesina and Drazen 1989).…”
Section: 2 Government Fragmentation and Fiscal Outcomessupporting
confidence: 80%
“…The effect of ideology on public debt is less obvious, however. While expansionary fiscal policies might on the one hand lead to more spending, some authors argue that left-wing parties are also more likely to increase taxes, with no obvious effect on the level of indebtedness (Borrelli and Royed 1995). We therefore have no strong priors with regard to the sign of the estimated coefficient.…”
Section: Dependent and Independent Variablesmentioning
confidence: 99%
“…2 However, excepting empirical work exploring the tax-smoothing model of Barro (1979) and Lucas and Stokey (1983), few have tested the many theories purporting to explain Figure 1. Recent empirical attention (Roubini and Sachs 1989ab;Edin and Ohlsson 1991;de Haan andSturm 1994, 1997;Borrelli and Royed 1995;de Haan et al 1998) focuses on theories of weak government and delayed stabilization. Others (von Hagen 1992;Harden 1994,1996;Hallerberg and von Hagen 1996;and de Haan et al 1997) stress budgetary rules and institutions or bicameralism and partisan differences between the chambers (Heller 1998).…”
mentioning
confidence: 99%